Fabrication of microlens arrays on soda-lime glass using a laser direct-write technique and a thermal treatment assisted by a CO2 laser. (October 2015) - Delgado, Tamara; Nieto, Daniel; Flores-Arias, María Teresa
Abstract: A low-cost method for fabricating microlens arrays on commercial soda-lime glass is presented. The hybrid technique is composed by a laser direct writing technique and a laser assisted post-thermal treatment. In particular we use a nanosecond Q-Switch Nd:YVO4 laser for fabricating the initial structure of microposts on soda-lime glass substrates and a CO2 laser combined with a furnace for reshaping and improving its morphological and optical qualities. This new fabrication approach lets us obtain a high quality microlenses array with a diameter of 50 μm, sag 1.5 μm, focal length 1 mm and a spot size of 7.8 μm. Furthermore, the proposed technique preserves the advantages of the laser direct-write technique in terms of design flexibility, simplicity, fast prototyping, low cost and so on; while the alternative laser assisted thermal treatment lets us overcome the bounding problems presented in other conventional thermal treatments. Highlights: We have developed a low cost process for fabricating microlens arrays on glass. The hybrid technique is composed for a laser direct write and a post thermal treatment. We avoid the bounding problems typical of conventional thermal treatments.